Georgia Architectural and Historic Properties Survey of 423 Mills St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 423 Mills St., Valdosta, Ga., December 1980. One story house of rectangular plan with gabled roof, shed porch with square posts; clapboard siding. Interior chimney. Set on brick piers. Double hung sash windows with 2/2 lights. Fair condition. Date of Construction: App. 1920. Located on a dirt lane with other similar houses. Significant as part of a potential N.R. district which covers 4 or 5 blocks.
Georgia Architectural and Historic Properties Survey of 423 Mills St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 81.0 MB (84,957,607 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)